Ginseng and Aspirin : Health Care Alternatives for Aging Chinese in New York - Guo, Zibin (Book collections on Project MUSE., 2018)
Navigating the maze of modern American health care is rarely easy; those who enter it are confronted with a dizzying array of specialists, practitioners, and clinics from which to choose, and are forced to make decisions regarding drugs and treatments about which they may know very little. For immigrants, finding their way can be difficult--especially for those to whom Western medicine is itself unfamiliar.In this engaging, accessible, and detail-rich book, Zibin Guo narrates elderly Chinese immigrants' response to contemporary American medicine. Traditional Chinese medicine emphasizes self-care and the medicinal value of foods and herbs; American doctors' responses to the ailments of their Chinese patients can seem impersonal and unnecessarily interventionist. Distrust, expense, and problems of communication and interpretation often frustrate both patient and practitioner.Guo paints a picture of a population that, despite its outward appearance of homogeneity, demonstrates a surprisingly wide variety of health-care knowledge, practice, and belief. Using case materials and interviews, he analyzes the blend of folk treatments and respect for Western science that coexist in the health care regimens of these elderly Chinese immigrants.